Potensi polisakarida xanthan dari fermentasi xanthomonas campestris sebagai pengembangan edible film dalam perlindungan struktur daging mentah - Annisa Nur Baety; Aulia Robiatul Adawiyah; Dyta Dwi Ardiana (Institute for Advanced Social, Science, and Sustainable Future, 2024)
Background: Meat is one of the important food sources to meet nutritional needs, especially protein. Improper storage of meat can cause microbes that cause meat to rot quickly. Findings: In the Indonesian food industry, meat storage generally still uses synthetic polymer plastic that is difficult to decompose by soil microbes and can pollute the environment. The purpose of writing this scientific paper is to overcome problems in the food industry, especially in the quality of raw meat that is easily rotten due to improper packaging. Methods: The method of writing this paper is by conducting a literature search from data and information contained in books, scientific journals, and several libraries that can be used as relevant sources. Data and information are taken by collecting data as reference materials and analysis, then the information is processed using a descriptive analysis method based on secondary data to be developed into a unified material so that a solution and conclusion can be obtained. In this era of industry 5.0, edible film based on xanthan polysaccharide (Xanthomonas campestris) will be very effective, solution-oriented, and help Indonesia in overcoming problems in the food industry. Conclusion: The development of edible film based on xanthan polysaccharide (Xanthomonas campestris) will create an innovation in food packaging that can maintain the quality of raw meat and is environmentally friendly. The next step is to disseminate information to the public regarding environmentally friendly plastic substitute products as raw meat packaging.